Comparison of the effectiveness of late-phase clinic-based and home-based progressive resistance training in female patients with total knee arthroplasty - Alsayani, Khaled Yahya Abdullah; Aslan, Ummuhan Bas; Bayrak, Gokhan; Savkin, Raziye; Buker, Nihal; Gungor, Harun Resit (Taylor & Francis Inc, 2023)
Background: Early rehabilitation after total knee arthroplasty (TKA) is crucial in functional outcomes. However, considering improvements in the first six months, there may be benefits to continuing rehabilitation beyond three months postoperatively to achieve maximum functionality and strength.Objective: The aim was to compare: (a) effectiveness of late-phase clinic-based and home-based progressive resistance training (PRT) in female patients with TKA; and (b) crude cost of both interventions and explore feasibility.Methods: Thirty-two patients were assigned to clinic-based PRT (n = 16) and home-based PRT (n = 16) groups. A training program was performed at the clinic or at home for eight weeks. Pain, quadriceps and hip abductor strength, patient-reported and performance-based outcomes, knee range of motion (ROM), joint awareness, quality of life (QoL) were assessed at baseline (three months postoperatively) and after 8-week intervention (five months postoperatively). Feasibility and crude cost were examined.Results: Exercise adherence was 100% in clinic-based PRT and 90.6% in the home-based PRT group. Both interventions improved quadriceps and hip abductor muscle strength, performance-based and patient-reported outcomes, knee ROM, and joint awareness without side effects (p < .05). Clinic-based PRT showed better results in: activity pain (p = .004, ES = -0.888); knee flexion (p = .002, ES = 0.875) and extension ROM (p = .004, ES = -1.081); chair sit-to-stand test (p = .013, ES = 0.935); joint awareness (p = .008, ES = 0.927); and QoL than home-based PRT (p < .05).Conclusion: Late-phase clinical-based and home-based PRT interventions may be beneficial in improving muscle strength and functionality in patients with TKA. Late-phase PRT is feasible, cost-effective, and recommended for rehabilitation after TKA.
Keywords: Total Knee Arthroplasty; Physical Therapy; Progressive Resistance Training; Clinic-Based Exercise; Home-Based Exercise; Quality-Of-Life; Total Hip; Functional Limitations; Muscle Impairments; Physical Function; Strength; Rehabilitation; Exercise; Program; Replacement